Halal Tourism as a New Perspective: An Analysis of Developments in Southeast Sulawesi: Halal Tourism as a New Perspective: An Analysis of Developments in Southeast Sulawesi - Hugua; Achmad, Mansyur; Rowa, Hyronimus (IKONOMIKA, 2025)
Post-COVID-19, Southeast Sulawesi’s tourism sector has exhibited signs of recovery; however, its contribution to national tourist arrivals and regional revenue remains marginal. Given the region’s predominantly Muslim population, integrating a halal tourism framework encompassing prayer facilities, halal-certified culinary offerings, and Sharia-compliant activities is increasingly imperative. This study examines tourism development in Kendari City, a mainland urban area, and in Wakatobi Regency, an archipelagic region designated as a National Tourism Strategic Area (KSPN) under the program. Adopting a descriptive qualitative method underpinned by Push-Pull and Stakeholder theories, this research utilizes interviews, observations, document analysis, and FGDs with policymakers, business actors, academics, media, and tourists. Findings indicate that tourist motivations are primarily driven by adventure and bleisure travel, with marine biodiversity and cultural heritage serving as primary attractions. Critical constraints include high travel costs, limited accessibility, and unmet expectations regarding cultural events, infrastructure, and public amenities. Achieving sustainable tourism requires synergistic stakeholder collaboration, improved budget allocation, enhanced promotion, and a structured integration of halal tourism to strengthen competitiveness and support local development.